2014
DOI: 10.1210/en.2014-1105
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pituitary Actions of TAC3 Gene Products in Fish Model: Receptor Specificity and Signal Transduction for Prolactin and Somatolactin α Regulation by Neurokinin B (NKB) and NKB-Related Peptide in Carp Pituitary Cells

Abstract: TAC3 is a member of tachykinins, and its gene product neurokinin B (NKB) has recently emerged as a key regulator for LH through modulation of kisspeptin/GnRH system within the hypothalamus. In fish models, TAC3 not only encodes NKB but also a novel tachykinin-like peptide called NKB-related peptide (NKBRP), and the pituitary actions of these TAC3 gene products are still unknown. Using grass carp as a model, the direct effects and postreceptor signaling for the 2 TAC3 products were examined at the pituitary lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
49
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 52 publications
5
49
1
Order By: Relevance
“…In addition, we provide the first evidence that NKBs up-regulate hormone gene expression in a fish model. A recent study in grass carp demonstrated that NKBs did not have effects on LH production in primary cultures of pituitary cell, but stimulated prolactin and somatolactin a synthesis and secretion from the pituitary (Hu et al, 2014). Thus, it is possible the NKBs regulate gonadotropin subunit mRNA expression indirectly via their effects on GnRH.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we provide the first evidence that NKBs up-regulate hormone gene expression in a fish model. A recent study in grass carp demonstrated that NKBs did not have effects on LH production in primary cultures of pituitary cell, but stimulated prolactin and somatolactin a synthesis and secretion from the pituitary (Hu et al, 2014). Thus, it is possible the NKBs regulate gonadotropin subunit mRNA expression indirectly via their effects on GnRH.…”
Section: Discussionmentioning
confidence: 99%
“…Given that (i) two somatolactin isoforms, SLα and SLβ, have been previously shown to trigger SLα secretion and gene expression at the pituitary level7, and (ii) TAC3a gene products could also stimulate SLα secretion and gene expression via activation of NK3R in carp pituitary cells14, we examined the functional interaction between TAC3a gene products and SLs in their stimulatory activity on SLα gene expression. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the studies in mammals (e.g., rodent and sheep), NKB was found to be a key regulator for GnRH pulsatility and downstream LH release via NK3R activation in kisspeptin neurons located in the arcuate nuclei within the hypothalamus3031. Similar investigations have been recently extended to fish models with the novel findings that the TAC3 gene in fish species, e.g., in zebrafish323334, goldfish35, tilapia36 and grass carp14, not only encodes NKB as the gene product, but also the mature peptide of a new member of tachykinin called NKB-related peptide (NKBRP). Similar to NKB, NKBRP was also effective in stimulating LH release, e.g., in zebrafish32, goldfish35 and tilapia36, suggesting the reproductive function of TAC3 gene products was well conserved throughout vertebrate evolution.…”
mentioning
confidence: 89%
See 2 more Smart Citations